Antibody-pHPMA functionalised fluorescent silica nanoparticles for colorectal carcinoma targeting - Lizoňová, Denisa; Majerská, Monika; Král, Vlastimil; Pechar, Michal; Pola, Robert; Kovář, Marek; Štěpánek, František (RSC advances, 2018)
The systemic application of highly potent drugs such as cytostatics poses the risks of side effects, which could be reduced by using a carrier system able to specifically deliver the encapsulated drug to the target tissue. Essential components of a nanoparticle-based drug delivery system include the drug carrier itself, a targeting moiety, and a surface coating that minimizes recognition by the immune system. The present work reports on the preparation, in vitro characterization and in vivo testing of a new delivery system consisting of fluorescent silica nanoparticles functionalised with a non-immunogenic stealth polymer poly(N-(2-hydroxypropyl)methacrylamide) (pHPMA) and a monoclonal antibody IgG M75 that specifically binds to Carbonic Anhydrase IX (CA IX). CA IX is a promising therapeutic target, as it is a hallmark of several hypoxic tumours including colorectal carcinoma. Uniquely in this work, the monoclonal antibody was covalently coupled to the surface of fluorescently labelled silica nanoparticles via a multivalent amino-reactive co-polymer rather than a traditional bivalent linker. The pHPMA-M75 functionalised SiO2 nanoparticles exhibited excellent colloidal stability in physiological media. Their in vitro characterisation by flow cytometry proved a highly specific interaction with colorectal carcinoma cells HT-29. In vivo study on athymic NU/NU nude mice revealed that the SiO2-pHPMA-M75 nanoparticles are capable of circulating in the blood after intravenous administration and accumulate in the tumour at tenfold higher concentration than nanoparticles without specific targeting, with a considerably longer retention time. Additionally, it was found that by reducing the dose administered in vivo, the selectivity of the nanoparticle biodistribution could be further enhanced in favour of the tumour.